The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2019
DOI: 10.1002/1438-390x.12020
|View full text |Cite
|
Sign up to set email alerts
|

Habitat loss‐induced tipping points in metapopulations with facilitation

Abstract: Habitat loss is known to pervade extinction thresholds in metapopulations. Such thresholds result from a loss of stability that can eventually lead to collapse. Several models have been developed to understand the nature of these transitions and how they are affected by the locality of interactions, fluctuations or external drivers. Most models consider the impact of grazing or aridity as a control parameter that can trigger sudden shifts, once critical values are reached. Others explore instead the role playe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 47 publications
(58 reference statements)
1
19
1
Order By: Relevance
“…Also, facilitation processes (involving strong nonlinearities) are known to introduce important changes in spatial systems, as compared with well-mixed ones. In this sense, recent research has found a shift from catastrophic tipping points to continuous ones, due to local spatial processes [42,43]. Similar analyses to those presented in figure 2 for the mean-field model are displayed in figure 3 for the CA simulations.…”
Section: Spatial Stochastic Modelsupporting
confidence: 71%
See 4 more Smart Citations
“…Also, facilitation processes (involving strong nonlinearities) are known to introduce important changes in spatial systems, as compared with well-mixed ones. In this sense, recent research has found a shift from catastrophic tipping points to continuous ones, due to local spatial processes [42,43]. Similar analyses to those presented in figure 2 for the mean-field model are displayed in figure 3 for the CA simulations.…”
Section: Spatial Stochastic Modelsupporting
confidence: 71%
“…This is a dynamical phenomenon that involves extremely long transients once the bifurcations has occurred, and the time trajectories experience a long bottleneck before rapidly achieving, in equations (3.5) and (3.6), another attractor (the full desert state in electronic supplementary material, figure S6(a) and (b)). These long transients [63] are typically found in systems with strong feedbacks, such as cooperation, catalytic processes [64,65] or metapopulations with facilitation [43]. Also, this dynamical delay tied to saddle-node bifurcations has been recently described in both deterministic and stochastic well-mixed approaches for the non-terraformed system explored in this article (see [19] for more details).…”
Section: Mean-field Modelmentioning
confidence: 70%
See 3 more Smart Citations